2003
DOI: 10.2466/pms.2003.97.3.805
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Public Restroom Handwashing Behavior Associated with Visual Behavior Prompts

Abstract: Handwashing after using the restroom is generally poor across the population, and one common method used to increase the frequency of handwashing is to place signs reminding individuals to wash their hands. The current study examined the association between the absence and presence of signs reminding one to wash their hands and handwashing in public restrooms. Signs prompting handwashing behavior remind restroom patrons of acceptable behavior, and the presence of these signs is hypothesized to be associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 13 publications
11
68
3
7
Order By: Relevance
“…(EPITeen Cohort, 2003 Although some significant differences were found by gender in the frequency of washing hands, in general the differences were small. Opposite to our study, several studies report that women more frequently wash their hands, particularly after using the toilet (Guinan et al 1997;Snow et al 2006;Johnson et al, 2003). On the other hand, men tend to overestimate the frequency of washing (Guinan et al 1997;Snow et al 2006;Johnson et al 2003), which may explain the results in our study since they are based on self-reported data.…”
Section: Discussioncontrasting
confidence: 70%
“…(EPITeen Cohort, 2003 Although some significant differences were found by gender in the frequency of washing hands, in general the differences were small. Opposite to our study, several studies report that women more frequently wash their hands, particularly after using the toilet (Guinan et al 1997;Snow et al 2006;Johnson et al, 2003). On the other hand, men tend to overestimate the frequency of washing (Guinan et al 1997;Snow et al 2006;Johnson et al 2003), which may explain the results in our study since they are based on self-reported data.…”
Section: Discussioncontrasting
confidence: 70%
“…These findings may be explained by the autonomy of physicians in Hong Kong society, while nurses, as females, are more influenced by their superior's expectation. This explanation is supported by the results of Johnson et al, who concluded that the higher hand hygiene compliance of females was associated with their tendency to practice socially acceptable behavior [32], whereas Cantrell et al stated that the heterogeneity in physicians' hand hygiene compliance among sites within the same institution was consistent with the important role of the local ward culture in terms of perceived vulnerability of patients and role modeling by senior physicians in different settings [33]. All of these studies support the conclusion that subjective norms are the most important cognitive factor influencing an individual to perform good hand hygiene behavior.…”
Section: Variablesmentioning
confidence: 53%
“…The implemented regression models show that women are more successful than men. In a number of studies, it is common that women have higher frequencies than men when handwashing is considered [17,23,33,[36][37][38]. It seems that structuring the health behaviors by gender roles reveals itself in determination of handwashing.…”
Section: Determinants Of Handwashing Behaviormentioning
confidence: 99%